The Importance of Autumn Rye in the National Economy - Maftuna Abdimuminova Alisher qizi (Zien Journals, 2022)
The article describes the morphological features of autumn rye, as well as all the nutritional products that are constantly necessary for human life in them, including protein, starch, vitamins, carbohydrates, oil, destrin, mineral salts, calcium, carbonated water and other biologically active substances.information is provided.
Keywords: Autumn rye; root; moisture